PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN PEMAHAMAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERATING PADA DINAS KESEHATAN KABUPATEN BONDOWOSO - Susanto, Herman; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to determine and analyze the use of information technology and understanding of the regional financial accounting system on the quality of financial reports with the internal control system as a moderating variable at the Bondowoso District Health Service. This research method uses quantitative methods. This research was conducted for three months, namely from May to July 2023. The population in this study was 45 Bondowoso District Health Service employees. The research chose a saturated sampling technique because the population was relatively small, so the sample in this study used the entire population as respondents, 45 ASN in the PNS and P3K categories. Researchers used Structural Equation Model - Partial Least Square (PLS-SEM) to analyze data and test hypotheses in this research. The research results show that the use of information technology has a significant positive effect on the quality of financial reports; Understanding the regional financial accounting system has a significant positive effect on the quality of financial reports; The internal control system has a significant positive effect on the quality of financial reports at the Bondowoso District Health Service; The internal control system positively and significantly moderates the influence of the use of information technology on the quality of financial reports; The internal control system positively and significantly moderates the influence of understanding the regional financial accounting system on the quality of financial reports.